DAMPAK PERUBAHAN ORGANISASIONAL INSTITUSI PENDIDIKAN TINGGI KESEHATAN DALAM PERSPEKTIF MANAJEMEN - Nang Randu Utama (Universitas Negeri Malang, 2017)
Abstract: This study aims to obtain a picture of the impact of organizational changes in the institution of higher health education in the management perspective that occurred in the scope of educational institutions belong to the Ministry of Health of the Republic of Indonesia. This study used a qualitative approach by conducting case study at Palangka Raya Health Polytechnic. The results of the study are as follows: (1) organizational change resulted in changes in the organizational structure; (2) organizational change also resulted in changes in the construction of facilities and infrastructure; (3) work system is no longer leads to routine, more dynamic, and flexible; (4) efficiency in learning and budget planning is done through a single door and centralized including personnel affairs, finance and general administration (ADUM) and academic and student affairs administration (ADAK); (5) organizational change is also accompanied by changes in the behavior of members of the organization, (6) organizational change is also related to leadership factors; and (7) organizational change also affect all forms of services that exist within the organization. Keyword: change, organizational change, health polytechnic Abstrak: Penelitian ini bertujuan untuk memperolah gambaran mengenai dampak perubahan organisasional institusi pendidikan tinggi kesehatan dalam perspektif manajemen yang terjadi di lingkup institusi pendidikan Kementerian Kesehatan Republik Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan studi kasus pada institusi Politeknik Kesehatan Kemenkes Palangka Raya dalam perspektif manajemen. Hasil penelitian adalah: (1) perubahan organisasi mengakibatkan perubahan pada struktur organisasi; (2) perubahan organisasi juga mengakibatkan perubahan pada pembangunan sarana dan prasarana; (3) perubahan pada sistem kerja yang tidak lagi mengarah pada rutinitas, namun lebih dinamis, dan fleksibel; (4) terjadi efisiensi dalam pembelajaran dan perencanaan anggaran yang dilakukan melalui satu pintu dan terpusat termasuk Urusan Kepegawaian, Keuangan dan Administrasi umum (ADUM) dan Administrasi Akademik dan Kemahasiswaan (ADAK); (5) perubahan organisasi juga disertai dengan perubahan perilaku anggota organisasi;   DOI: https;//doi.org/10.17977/um025v1i32017p187